A NEW EARLY COELOPHYSOID NEOTHEROPOD FROM THE LATE TRIASSIC OF NORTHWESTERN ARGENTINA (Ameghiniana, 2017)
Neotheropoda represents the main evolutionary radiation of predatory dinosaurs and their oldest members are Late Triassic in age. The Triassic neotheropod record is restricted to North America and Europe with the exception of a few specimens from South America, which includes a single species ?Zupaysaurus rougieri? and a yet unnamed form. Here, the South American record of the group is enriched with the description of the new genus and species Powellvenator podocitus from the middle Norian Los Colorados Formation (Ischigualasto-Villa Unión Basin) of northwestern Argentina. The new taxa are represented by previously undescribed partial hindlimbs collected by J. F. Bonaparte and associated to the hypodigm of the pseudosuchian Riojasuchus tenuisceps. In addition, a specimen originally interpreted by Bonaparte in 1972 as an indeterminate coelurosaur is here referred to the new species. Powellvenator podocitus differs from other basal dinosaurs in character-states that include an astragalus with a distinctly sigmoid posterodorsal margin and a rounded dorsal expansion on the anteromedial portion of the astragalar body in anterior view, calcaneum with a laterally projected flange, and strongly reduced shaft of metatarsal II. The phylogenetic relationships of the new species were tested in one of the most comprehensive analyses focused on early neotheropods, which recovered Powellvenator podocitus within Coelophysoidea and as the sister-taxon of Coelophysidae. Powellvenator podocitus represents the first coelophysoid from South American together with a preliminary reported form from the Marayes-El Carrizal Basin.